The typical triad of idiopathic normal pressure hydrocephalus in a 62-year-old male: a case report - Naela Bader Alamoudi; Ruba Khalid Alnajim; Dunia Alfaraj (Saudi Journal of Emergency Medicine, 2020)
Normal pressure hydrocephalus is a rare pathological condition of the brain where the cerebrospinal fluid accumulates in the ventricles thus enlarged, but with normal opening pressure on lumbar puncture. This results in three classical symptoms, namely, progressive mental impairment, gait disturbance, and urinary or bowel incontinence. It most commonly occurs in adults over the age of 60 years. It could be extremely misdiagnosed by many clinicians since the symptoms resemble other neurodegenerative disorders. Here, we are reporting a case of idiopathic Normal Pressure Hydrocephalus who was brought to the Emergency Department after falling down on the floor complaining of an imbalanced gait, with the typical triad of the aforementioned symptoms. He is a known case of diabetes mellitus. His walking problem was thought to be a complication of his diabetic foot and he had physical therapy for that, but it kept worsening with time. His gait was shuffling and brady-kinetic, with mild drifting toward the right side. The coordination was abnormal. All laboratory investigations were normal. A head CT revealed brain tissue volume loss with disproportionate dilation of the lateral and third ventricles. The patient refused lumbar puncture and so the diagnosis of NPH was made. Conn's stated, in his point of view, in a report where he was an NPH patient, that patients themselves and their families have the final decision of whether or not shunt surgery should be undertaken, rather than by their physicians [Conn H. Normal pressure hydrocephalus: a case report by a physician who is the patient. Clinical Medicine. 2007;7(3):296-299. https://doi.org/10.7861/clinmedicine.7-3-296] [SJEMed 2020; 1(1.000): 34-34]